2017
DOI: 10.1371/journal.pone.0187941
|View full text |Cite
|
Sign up to set email alerts
|

How does trust affect acceptance of a nuclear power plant (NPP): A survey among people living with Qinshan NPP in China

Abstract: It is difficult to know whether different dimensions of trust have different effects on local residents’ acceptance of nuclear power plants (NPPs). In previous research such trust has been considered as a single dimensional concept. This paper divides trust into goodwill trust and competence trust, and we explore the ways in which trust affects acceptance of NPPs through structural equation modeling. A survey of 491 people was conducted in Haiyan County, China, where the Qinshan nuclear power plant is located.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 44 publications
3
28
0
Order By: Relevance
“…In a cross-cultural investigation of 23 activities and technological hazards, trust in regulatory organizations is found to be directly and indirectly linked with public acceptance, and perceived benefit plays a more important role than perceived risk in mediating the trust-acceptability casual chain [58]. Regarding nuclear power plants (NPPs), goodwill trust improves acceptance of NPPs by decreasing risk perception, while competence trust improves the acceptance by increasing benefit perception [59]. However, these findings are challenged by the associationist model of trust (AMT), which asserts that acceptance drives both trust and risk perception [60,61].…”
Section: Trust and Fairnessmentioning
confidence: 99%
“…In a cross-cultural investigation of 23 activities and technological hazards, trust in regulatory organizations is found to be directly and indirectly linked with public acceptance, and perceived benefit plays a more important role than perceived risk in mediating the trust-acceptability casual chain [58]. Regarding nuclear power plants (NPPs), goodwill trust improves acceptance of NPPs by decreasing risk perception, while competence trust improves the acceptance by increasing benefit perception [59]. However, these findings are challenged by the associationist model of trust (AMT), which asserts that acceptance drives both trust and risk perception [60,61].…”
Section: Trust and Fairnessmentioning
confidence: 99%
“…To identify the determinants of the public's WTP for replacing nuclear power, it is necessary to first consider the covariates which should be included in the model. Existing studies found that a variety of psychological, emotional, and socio-demographic factors influence the acceptance of nuclear power [14][15][16][17][18][19], and we select a few covariates with reference to these studies. Table 3 summarizes the basic statistics of the covariates included in Model 2.…”
Section: Estimation Results: Public Acceptance For Reducing Nppsmentioning
confidence: 99%
“…Since 2010, related studies have been rapidly increasing and have introduced diverse perspectives on the issue. Examples include; proposing new indicators that quantify public acceptance of nuclear power [7], analyzing the impact of the Fukushima disaster on the acceptance of nuclear power [8][9][10][11], identifying public attitude on nuclear power using social media data [12], suggesting an international comparison of public acceptance of nuclear energy [13], and identifying the determinants of acceptance of nuclear power [14][15][16][17][18][19].…”
Section: Literature Reviewmentioning
confidence: 99%
“…This causal model has been widely used to explain public acceptance in a variety of technological domains, such as gene technology [ 18 , 39 , 40 , 41 ], financial technology [ 42 , 43 ], nanotechnology [ 44 , 45 , 46 , 47 , 48 , 49 ], renewable energy [ 32 , 50 , 51 , 52 ], unmanned aircraft [ 53 ], and automated driving technology [ 54 , 55 ]. The present study is also based on Siegrist’s causal model.…”
Section: Research Hypotheses and Frameworkmentioning
confidence: 99%
“…Several studies have found that these two types of social trust have different antecedents. The level of trust in public organizations depends on their abilities and competence, and the level of trust in industrial organizations depends on their intentions, honesty, and integrity [ 31 , 32 ]. At the same time, some studies found that public trust in these two types of trustees differ: people have more trust in public organizations than in industrial organizations [ 33 ].…”
Section: Introductionmentioning
confidence: 99%